Mixed effects of complement in a chronic murine model of inflammatory erosive arthritis and pulmonary vascular disease - Kiana L. Chen; Stacey Duemmel; Michael Christof; Gaochan Wang; H. Mark Kenney; Marc Nuzzo; Qingfu Xu; Benjamin Korman; Homaira Rahimi (PLoS ONE, 2026)
Complement’s role in the pathology of rheumatoid arthritis and pulmonary hypertension (PH) is not fully understood. We aimed to determine whether complement deficiency is protective against joint and lung disease using the tumor necrosis factor-transgenic (TNF-Tg) mouse model characterized by chronic inflammatory-erosive arthritis and PH. TNF-Tg synovium and lungs were analyzed with bulk and single-cell RNA-sequencing. TNF-Tg mice were crossed with complement component 3 knockout (C3KO) and factor B knockout (fBKO) mice to quantify disease. Knee histology was scored, CD45 + Ly6C-C5aR1 + cells were quantified by flow cytometry, mid-hindpaw bone volumes were determined with micro-computed tomography, and lung disease was quantified with histology and right heart catheterization. TNF-Tg mice have upregulated complement-related genes, however, C3 and fB knockout did not cause significant changes in pathology. Synovium from C3KO TNF+ mice had a greater C5aR1 + cell population than TNF-Tg mice ( p < 0.0001 ). In early disease, C3KO TNF+ mice exhibited greater bone volumes ( p < 0.05, p < 0.01) than other TNF+ mice. Complement deficiency in a chronic inflammatory model does not ameliorate joint or pulmonary disease. However, C3 deficiency may delay complement-dependent bone erosions. The influence of complement on disease may change with persistent inflammation. Chronic TNF-mediated disease may represent a pathologic endotype that is differentially mediated by complement.